Resistance Status of Aedes albopictus (Skuse) on Malathion in Bengkulu City - Triana, Dessy; Umniyati, Sitti Rahmah; Mulyaningsih, Budi (Universitas Negeri Semarang in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2018)
Abstract Dengue Hemorrhagic Fever (DHF) is a disease caused by dengue virus and transmitted by Aedes aegypti mosquito as the main vector and Aedes albopictus as secondary vector. In 2016, Bengkulu City was one of 3 cities that experiencing DHF outbreaks in Indonesia. Insecticides malathion have been used since 1990 in bulk in DHF control programs in Bengkulu City and have not had an evaluation report on Aedes sp. vulnerability to malathion. The purpose of this research was to know the resistance status of Ae albopictus mosquitoes from endemic and sporadic areas of DHF in Bengkulu City to malathion. The sample of the study was the Ae. albopictus adult female mosquitoes which collected from endemic and sporadic areas of DHF in Bengkulu City with ovitrap installation. The resistance test was performed by CDC Bottle Bioassay method with malation 96% and 50 μg/ml diagnostic dose of. The results of this study showed 1% mortality on endemic area and 5% on sporadic area. Aedes albopictus of both areas were resistant to malathion.   Keywords: Ae. albopictus, bottle bioassay, malathion.   Abstrak Demam Berdarah Dengue (DBD) merupakan penyakit yang disebabkan oleh virus dengue dan ditularkan oleh nyamuk Aedes aegypti sebagai vektor utama dan Aedes albopictus sebagai vektor sekunder. Pada tahun 2016, Kota Bengkulu merupakan 1 dari 3 kota yang mengalami KLB DBD di Indonesia. Insektisida malation telah digunakan sejak tahun 1990 secara massal dalam program pengendalian DBD di Kota Bengkulu dan belum memiliki laporan evaluasi mengenai kerentanan Aedes sp terhadap malation. Tujuan penelitian untuk mengetahui status kerentanan nyamuk Ae. albopictus dari daerah endemis dan sporadis DBD Kota Bengkulu terhadap malation. Sampel penelitian adalah nyamuk betina dewasa Ae. albopictus yang dikoleksi dari daerah endemik dan sporadis DBD Kota Bengkulu dengan pemasangan ovitrap. Uji kerentanan dilakukan dengan metode CDC Bottle Bioassay dengan malation 96% dan dosis diagnostik 50 µg/ml. Hasil penelitian ini  menunjukkan mortalitas 1% untuk daerah endemis dan 5% untuk daerah sporadis. Aedes albopictus kedua daerah telah resisten terhadap malation.   Kata Kunci: Ae. albopictus, bottle bioassay, malation.